2005
DOI: 10.1016/j.femsle.2005.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Adammutant ofYersinia pestisis attenuated and induces protection against plague

Abstract: We have constructed a dam mutant of Yersinia pestis GB. In BALB/c mice inoculated subcutaneously, the median lethal dose of the mutant was at least 2000-fold higher than the wild type. Mice inoculated with sub-lethal doses of the mutant were protected against a subsequent challenge with virulent Y. pestis. The effect of dam inactivation on gene expression was examined using a DNA microarray, which revealed increased expression of a number of genes associated with the SOS response. These results confirm the key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 19 publications
1
62
0
1
Order By: Relevance
“…In addition to genetic factors, it should also be noted that epigenetic factors may also play important roles in fitness and pathogenesis. The influence of DNA adenine methylation on virulence has been demonstrated for various pathogens, including Vibrio cholerae (45), Salmonella enterica (46), Yersinia pestis (47), and Mycobacterium tuberculosis (48). The methylation of DNA at specific sites may exert influences through the regulation of chromosome replication, transcriptional regulation, and mismatch repair in response to various environmental stimuli (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic factors, it should also be noted that epigenetic factors may also play important roles in fitness and pathogenesis. The influence of DNA adenine methylation on virulence has been demonstrated for various pathogens, including Vibrio cholerae (45), Salmonella enterica (46), Yersinia pestis (47), and Mycobacterium tuberculosis (48). The methylation of DNA at specific sites may exert influences through the regulation of chromosome replication, transcriptional regulation, and mismatch repair in response to various environmental stimuli (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GATC methylation plays a role in the virulence of diverse pathogens, e.g. Salmonella enterica serovar Typhimurium, Vibrio cholerae, Yersinia pestis, and Yersinia pseudotuberculosis (Heithoff et al, 1999;Julio et al, 2001;Robinson et al, 2005). It has also been shown that the dam gene is essential for the viability of A. hydrophila SSU and that M. AhySSUDam is involved in A. hydrophila pathogenesis (Erova et al, 2006a(Erova et al, , b, 2012.…”
Section: Functional Analysis Of the Dna Methylation Enzymes Of Farm81mentioning
confidence: 99%
“…Transcription of the genes is controlled by the temperature and activity of the secretion apparatus (Cornelis, 2002;Viboud & Bliska, 2005). Anisimov, 2002a, b, Anisimov et al, 2004Brubaker, 1991;Oyston et al, 2000;Perry & Fetherston, 1997;Robinson et al, 2005;Sing et al, 2002;Sodhi et al, 2004 Infective doses of 10 bacteria or less are sufficient to cause lethal infection in naïve rodents and primates via the intradermal, subcutaneous and intravenous routes (Anisimov et al, 2004;Brubaker, 1991;Perry & Fetherston, 1997). LD 50 values in the case of the respiratory and oral routes of infection increase to 10 2 -10 4 c.f.u.…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%